Probability Measures for Estimated Data. - Thompson, William W.; Kemper, Earl L. (The Accounting Review, 1965)
Abstract In this article a general framework for converting subjective estimates into more significant data has been presented. The process of combining individual estimates into a more meaningful total has also been treated. Admittedly, results obtained through the use of this procedure are not highly sophisticated. Nevertheless, data obtained and presented in this manner are much more meaningful than those expressed as single-point estimates. In utilizing this approach, management is adding a new dimension to the data utilized in decision-making. It should be expected, then, that better decisions will be the result. In recent years considerable attention has been given to the problem of subjectivity as it relates to the estimated data for decision-making. Obviously, it is not possible to eliminate the subjective factor from estimated data. Yet, it is feasible and highly desirable to provide the decision maker with information relative to the statistical significance of these data. In effect, what is being suggested is that the traditional estimates of expected values be supplemented by corresponding estimates of variances.